2006
DOI: 10.1001/jama.295.24.2867
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Fusarium Keratitis Associated With Contact Lens Wear in Singapore

Abstract: A new and evolving epidemic of Fusarium keratitis associated with contact lens wear was found in Singapore. Physicians and eye care practitioners worldwide need to be aware of the likelihood of similar outbreaks emerging among contact lens wearers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
161
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(171 citation statements)
references
References 30 publications
6
161
0
3
Order By: Relevance
“…16 Previously published studies have also reported associations between certain multipurpose solution types and Fusarium and Acanthamoeba outbreaks of contact lens-related microbial keratitis. [25][26][27] Certain polymeric biguanide-based care solutions have been demonstrated to be less effective against bacterial biofilms in comparison with hydrogen peroxide or polyquaternium-based solutions. 28 In addition, reduction in microbial efficacy of this product has been reported when used for the storage of contact lenses in lens cases over a prolonged period of time.…”
Section: Discussionmentioning
confidence: 99%
“…16 Previously published studies have also reported associations between certain multipurpose solution types and Fusarium and Acanthamoeba outbreaks of contact lens-related microbial keratitis. [25][26][27] Certain polymeric biguanide-based care solutions have been demonstrated to be less effective against bacterial biofilms in comparison with hydrogen peroxide or polyquaternium-based solutions. 28 In addition, reduction in microbial efficacy of this product has been reported when used for the storage of contact lenses in lens cases over a prolonged period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium oxysporum keratitis has been reported to respond to treatment with tobramycin, 11 and in vitro studies have shown antibiotic inhibition of pectolytic and cellulolytic enzyme activity in F oxysporum by amoxycillin, and to a lesser extent by chloramphenicol, erythromycin and raficillin. 12 In the outbreak of Fusarium keratitis associated with contact lens wear that was recently reported from Singapore, 13 11 (16.2%) of the 68 eyes treated with topical antibiotics alone (gentamicin and cefalzolin) resolved ''without the need for specific antifungal therapy''. Fusarium spp was isolated from all 11 eyes.…”
Section: Duringmentioning
confidence: 99%
“…While the pathogenesis of contact lens-related Pseudomonas keratitis remains unclear, bacterial contamination of the eye appears to play a major role [2,20]. Although P. aeruginosa is the most important cause of contact lens-associated corneal ulcers, other bacteria, fungi, or Acanthamoeba may also cause this condition [1,[7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, the incidence of fungal keratitis is generally low and fungal infection in contact lens wearers is much rarer when compared with bacterial and Acanthamoeba keratitis. In July 2005, the Hong Kong Department of Health became aware of an [13] reported on an outbreak of contact lens-related Fusarium keratitis in Singapore. Initially, the epidemic was believed to have followed contamination of the Bausch & Lomb multipurpose solution by a single strain of Fusarium during manufacture or storage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation